Patterns of Multinationals’ Technological Strategies in Emerging Economies: Evidences from Brazil and India. - Franco, E; Ray, S; Ray, P (SLPTMD (Department of International Development, University of Oxford), 2009)
A key factor behind a country’s ability to attract knowledge-based foreign Investment is an institutional context oriented towards innovation. The development of such a context is not an easy task though: it requires not only an advanced domestic knowledge base, but also a policy and a management framework that can integrate local and foreign assets in the host-country innovation system. This is a challenging task for emerging economies, especially given that they have increasingly experienced erosion of their locale-specific technological advantages after liberalization of their economies. Hence there is a strong need to re-design strategies for catch-up, oriented towards combining interests of local and foreign business. This paper aims to contribute to the design of such new strategies by identifying Innovation Practices (IPs) of Multinational Enterprises (MNEs) affiliates in Brazil and India. Multivariate analysis techniques applied in more than 1000 manufacturing foreign-owned firms in Brazil and India shows significant differences in knowledge-based assetsseeking strategies by MNE affiliates, which reflect a heterogeneity of IPs in MNE affiliates acrosscountries. The results suggest MNEs have different levels of involvement with local innovation systems in Brazil and India. Such heterogeneity in assets-seeking MNEs behaviour combined with different country-specific competencies in attracting more-knowledge intensive foreign investments have created different opportunities for these countries to be inserted in the global value-chain.